Enhanced Electrokinetics of C−C Bond Splitting during Ethanol Oxidation by using a Pt/Rh/Sn Catalyst with a Partially Oxidized Pt and Rh Core and a SnO2 Shell. Issue 18 (4th September 2016) - Yang, Guangxing; Frenkel, Anatoly I.; Su, Dong; Teng, Xiaowei
Abstract: Direct ethanol fuel cells (DEFCs) are a promising technology for generating electricity through the electro‐oxidation of liquid ethanol. Its implementation requires the development of anode catalysts capable of producing CO2 and yielding 12‐electron transfer through breaking the C−C bond of ethanol. Here, we presented comprehensive studies of the electrokinetics of CO2 generation on Pt/Rh/Sn ternary catalysts. Our studies showed that the triphasic PtRhO x –SnO2 catalysts with a partially oxidized Pt and Rh core and a SnO2 shell, validated by X‐ray absorption analyses and scanning transmission electron microscope‐electron energy loss spectroscopy line scans, coincided with a 2.5‐fold increase in the CO2 generation rate towards ethanol oxidation reaction, compared with the biphasic PtRh‐SnO2 catalysts with a metallic PtRh alloy core and commercial Pt. These studies provided insight into the design of a new genre of electrocatalysts with a partially oxidized noble metal. Abstract : A partially oxidized Pt and Rh core with a SnO2 shell exhibited a much higher CO2 generation rate and CO2 selectivity than the PtRh alloyed core with SnO2 shell towards the electro‐oxidation of ethanol.